Epilepsy - A clinical approach (Portuguese Journal of Family Medicine and General Practice, 2005)
Epilepsies, by its frequency and multifaceted presentations, are a real challenge to the ability of physicians to arrive at diagnoses based on clinical methodology (almost) pure. The anamnesis the patient, families and witnesses implies prior knowledge of seizures and illnesses that are associated with seizures. We present the main thrust of the classifications in use and the prospects offered by new ways of seeing the síndromos epileptics. Indicate also the basis of the diagnostic process in its implications topographic, etiologic and therapeutic.